2016
DOI: 10.1038/srep31168
|View full text |Cite
|
Sign up to set email alerts
|

Environmental NO2 and CO Exposure: Ignored Factors Associated with Uremic Pruritus in Patients Undergoing Hemodialysis

Abstract: Uremic pruritus (UP), also known as chronic kidney disease–associated pruritus, is a common and disabling symptom in patients undergoing maintenance hemodialysis (MHD). The pathogenesis of UP is multifactorial and poorly understood. Outdoor air pollution has well-known effects on the health of patients with allergic diseases through an inflammatory process. Air pollution–induced inflammation could occur in the skin and aggravate skin symptoms such as pruritus or impair epidermal barrier function. To assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 43 publications
1
17
1
Order By: Relevance
“…In addition, abnormalities interactions between dermal mast cells and the distal ends of nonmyelinated C fibers may play a role in UP through the release of various triggering substances from mast cells, including histamine, proteases, interleukin-2, and tumor necrosis factor-α 12 . Several other factors have also been implicated in the pathogenesis of UP, including xerosis 2 , environmental air pollution 13 , inadequate dialysis 14 , serum phosphate 15 and magnesium 16 , iron deficiency anemia 17 , neuropathy and neurological changes 18 , hepatitis virus infection and others 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, abnormalities interactions between dermal mast cells and the distal ends of nonmyelinated C fibers may play a role in UP through the release of various triggering substances from mast cells, including histamine, proteases, interleukin-2, and tumor necrosis factor-α 12 . Several other factors have also been implicated in the pathogenesis of UP, including xerosis 2 , environmental air pollution 13 , inadequate dialysis 14 , serum phosphate 15 and magnesium 16 , iron deficiency anemia 17 , neuropathy and neurological changes 18 , hepatitis virus infection and others 2 .…”
Section: Discussionmentioning
confidence: 99%
“…30 Particulate matter is a complex mixture of liquid and solid droplets suspended in gas which comprises sulphates, nitrates, carbon compounds, various types of dust, biological contaminants and gaseous contaminants. [37][38][39] Consequently, PM 10 , SO 2 and NO 2 have acute influence on eczema outpatients. 31,32 Oxidative stress via excessive ROS production by particulate matter exposure increases pro-inflammatory cytokines, such as TNF-a and IL-8, and MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, exposure to NO 2 has been shown to damage the skin barrier function, thus increasing transepidermal water loss, and these factors worsen the skin symptoms and immunological function. [37][38][39] Consequently, PM 10 , SO 2 and NO 2 have acute influence on eczema outpatients. In addition, air pollution might increase the levels of aeroallergens and strengthen the effects of aeroallergens which are the trigger of exacerbations in eczema.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study also investigated the association between environmental exposure and uremic pruritus (UP), also known as chronic renal disease-related pruritus, among 866 patients undergoing hemodialysis. The researchers found that outdoor air pollution, including that from NO 2 and CO, was closely related to UP [ 12 ]. In addition, short- and long-term exposure to NO 2 has been shown to be significantly associated with respiratory and cardiovascular mortality [ 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have focused primarily on exposure to PM air pollution, represented by PM with an aerodynamic diameter of ≤ 10 μm (PM 10 ) or ≤ 2.5 μm (PM 2.5 ); no evidence has been reported regarding the association of renal function with other pollutants. Considering that exposure to other pollutants, such as nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), carbon monoxide (CO), and black carbons significantly associated with various diseases including CVD [ 3 , 5 , 11 , 12 ], an integrated analysis of air pollutants for renal function is important.…”
Section: Introductionmentioning
confidence: 99%